Predictors of Intent to Stay among Nursing Faculty Members: A Cross-sectional Study - Lay Lay Myint; Thitinut Akkadechanunt; Somjai Sirakamon; Bunpitcha Chitpakdee (Pacific Rim International Journal of Nursing Research, 2023)
The shortage of nursing faculty around the world is known to have an adverse effect on the quality of nursing education and the number of qualified nursing graduates. This is particularly alarming when globally, there is a shortage of millions of nurses in practice. Measuring the intent of nursing faculty to stay within academic settings is crucial in many countries to determine the state of the academic workforce and to strategize to address the issues. This cross-sectional study aimed to identify the predictors of intent to stay among 330 nursing faculty members randomly selected from 50 nursing and midwifery training schools in Myanmar, where nursing research is still in its infancy. The research instruments used were a demographic data form, Price’s Intent to Stay Scale, the Global Leadership Scale, the Work Autonomy Scale, the Workload Scale, the Faculty Stress Index, the Job Satisfaction Scale, and the Organizational Commitment Questionnaire. Data were analyzed using descriptive statistics, biserial correlation, and binary logistic regression analysis. The findings revealed that 68.5% of nursing faculty members reported a high intent to stay in their schools. Transformational leadership, workload, job stress, and organizational commitment were significant predictors of intent to stay, accounting for 39.2% of the variance. Job stress had the strongest negative effect on the intent to stay. Nursing faculty administrators, nursing and health leaders, and health policymakers can utilize the results of this study as baseline information to create effective strategies to improve transformational leadership, reduce workload and job stress, and promote organizational commitment among nursing faculty members to remain in academia.